Untersuchung der Prozesseinflussgrößen beim Presshärten des höchstfesten Vergütungsstahls 22MnB5 - Hoff, Cornelia (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2007)
Within the thesis the main influencing parameters during the different process steps of the hot stamping process as well as their interaction is examined. Emphasis is laid on the investigation of the heat transfer between blank and tool and the determination of the heat transfer coefficient during the different contact situations. In addition to that the characterization of the material properties of the steel 22MnB5 under the specific conditions of the hot stamping process is another focus of the wor